THE PRACTICAL ONE OF THE ATLETISMO IN THE MUNICIPAL SCHOOLS OF TERESINA-PI: A STUDY WITH THE INVOLVED PROFESSIONALS (Fiep Bulletin - online, 2014)
The study of qualitative nature of the analytical descriptive type it had as objective to investigate the atletismo as content of Physical Ed. in the municipal schools of Teresina-PI. The population was of 23 professors of Physical Education of Teresina-PI, in 32 investigated schools, corresponding 30% of a universe of 96 municipal schools. The sample was of the proportional probabilist type estratificada by municipal schools, being selected of random form. For collection of data a questionnaire with intuído was used to collect referring information to the identification data (sex, age, wage); porting activities (voleibol, basquete, atletismo, soccer, handebol) practised; participation in municipal and state pertaining to school competitions; material.The instrument was applied individually by the researchers. In function of the analytical and descriptive nature of the study, parametric procedures of analysis, percentage had been used. The results had indicated that 9 schools of 1ª 4ª series does not have professor of physical education. Of the professors who give it disciplines it 86% (n=20) are formed. Referring to the given porting content, 74% (n=17) are voleibol and 56% (n=13) are soccer. The atletismo was not cited. In the competitions of city 39% nine of the schools they participate, being that 22% five in the atletismo modality, 13% three of voleibol and 3 (13%) of soccer. How much to material 61% (n=14) they had declared to have material, 43% (n=10) to be enough and 56% (n=13) that the physical space is adjusted. One perceived a fallacy in the speech of the professors who had suggested more material and space for the practical one of atletismo. One concludes that bigger attention with the development of basic the motor abilities of these children would fit to the these professionals. One perceived that the pupil can be practising the modality in competitions without the had orientation. Finally, it fits to think us that this fact can be on to the formation of the professional, opening questionings for future works.
Keywords: Atletismo; pertaining to school content